The consequences of armed conflict on the health of women and newborn and sexual reproductive health – A position statement by the European Board and College of Obstetrics and Gynaecology (EBCOG). (July 2022) - Savona-Ventura, Charles; Mahmood, Tahir; Mukhopadhyay, Sambit; Martins, Nuno; Louwen, Frank; Tarlatzis, Basil
Abstract: Armed conflict brings about significant health-related consequences to the non-combatant population especially the elderly, women, and children. The consequences for women extend further than battle-related deaths. One important consequence of conflict is the population displacement resulting from individuals and families seeking safety in non-conflict zones. This forced migration places women at risk of gender-based violence during their journey and for this reason the host countries should ensure that the migrants are given access to reproductive health services, including providing emergency contraception and abortion. In the conflict zone, the collapse of all social support, including healthcare services, contribute towards a marked deterioration in the level of care provided to ensure reproductive health and safe motherhood. In addition, the community living the conflict zone is at an increased risk of community infectious disease and poor management of chronic illness. Women and children are almost always innocent victims of war. The international community must act effectively to primarily avoid conflict by sound diplomatic intervention and, when diplomacy fails, reduce the consequences of conflict.